Banking reputation and its impact on stock markets: A big data analysis through online comments. - Casado-Molina, Ana María; Rojas-de-Gracia, María Mercedes; Alarcón-Urbistondo, María del Pilar; Ramos, Célia M.Q. (Emerald, 2025)
Purpose Given the substantial number of social conversations on the Internet, companies must remain vigilant about protecting their reputations and businesses. The purpose of this research is to measure the impact on share prices of reputational variables, measured through online comments, at the banking sector level as well as patterns of behavior between these variables and fluctuations in share prices. Design/methodology/approach Using big data and business intelligence techniques, bank reputation was analyzed through online social comments. The sample includes seven Spanish banks. To measure the impact of reputational variables on share prices, an Online Reputation Index was created. These variables were then correlated and filtered with the share price variation rate of each bank on a daily basis under two scenarios: using all share price data and also focusing on times of sharp fluctuations. Finally, multiple linear regression analysis was used to identify patterns in these relationships. Findings The findings reveal that negative comments focusing on attitude, emotions and governance experiences – particularly regarding ethical performance – are the only reputational variables with a clear impact on share price fluctuations in the banking sector. Strong correlations between reputation variables and share prices were observed only when online comments were extremely negative. These behaviors were more frequent during periods of significant price fluctuations. Originality/value This is the first study to analyze the impact of the reputation of the banking sector measured in the online environment on share price, taking into account its multidimensional construct.
https://openpolicyfinder.jisc.ac.uk/id/publication/2713?from=single_hit
Keywords: Reputación digital; Bancos; Bolsa de valores; Datos masivos; Online perceptions; Reputational intelligence; Big data; Banking reputation; Stock market fluctuation; Share price